THE EFFECT OF COOPERATIVE LEARNING MODEL GROUP INVESTIGATION TOWARD LEARNING OUTCOMES PHYSICS VIEWED FROM LOGICAL THINKING ABILITY - Emilia Sari (Universitas Negeri Medan, 2017)
The purpose of research to determine: the results of physics learning with cooperative learning model type group investigation and conventional learning, learning outcomes physics that has the ability to think logically above average and the ability to think logically below the average as well as the interaction model of cooperative learning type group investigation and the ability to think logically in influencing the outcomes of learning physics. This research is quasi experimental. Technique that used to gain a sample is random cluster sampling. The instrument used is the science process skills test and test critical thinking skills.The results showed that: the learning outcomes of physics with cooperative learning model type group investigation better than conventional learning, learning outcomes physics that has the ability to think logically above average better than students who have the ability to think logically is below average and there is no interaction among cooperative learning model type group investigation and logical thinking skills in influencing the outcomes of learning physics.